Kindred spirits: Cognitive frame similarity and good faith provisions in strategic alliance contracts - Hanisch, Marvin; Graf-Vlachy, Lorenz; Haeussler, Carolin; König, Andreas; Cho, Theresa S. (Strategic Management Journal, 2025)
Research Summary: An intriguing yet underexamined phenomenon in strategic alliance contracts is the use of good faith provisions. These provisions appeal to parties' integrity and fair dealing but are often ambiguous, and their enforcement in court is unpredictable. Adopting a sociocognitive perspective, we predict a positive relationship between the similarity of partners' organizational-level cognitive frames and the number of good faith provisions in alliance contracts. We further posit that technological uncertainty strengthens this relationship, whereas each alliance partner's cumulative contracting experience weakens it. We also expect a more positive relationship in instances of “genuine” good faith, which serves as a substitute for an explicit clause, compared with “guarded” good faith, which supplements an explicit clause. Our analysis of 1225 strategic alliance contracts from the biopharmaceutical industry supports our arguments. Managerial Summary: Managers negotiating strategic alliances often face a dilemma: they negotiate detailed contracts to reduce legal risk but limit flexibility or opt for less codification, saving time and retaining flexibility but increasing legal risk. Good faith provisions offer a potential solution because they are flexible yet legally enforceable, but they require a shared interpretation of the relevant contingency, raising questions about when managers find this approach reasonable. We analyzed 1225 biopharmaceutical alliance contracts and found that such provisions are more common when alliance partners have similar cognitive frames, as evidenced by similar “About Us” web pages. This effect is stronger under conditions of greater technological uncertainty but weakens with more alliance experience. Our study elucidates the use of good faith provisions to aid managers in navigating alliance negotiations efficiently.
CRIS-Team Scopus Importer:2026-04-08
Keywords: cognitive frame similarity; contract design; good faith; interorganizational governance; social cognition; strategic alliances